Investigational new drugs for allergic rhinitis. (4th March 2017) - Ricketti, Peter A.; Alandijani, Sultan; Lin, Chen Hsing; Casale, Thomas B.
ABSTRACT: Introduction : Allergic rhinitis (AR) is a multifactorial disease characterized by paroxysmal symptoms of sneezing, rhinorrhea, postnasal drip and nasal congestion. For over a century, subcutaneous allergen immunotherapy (SCIT) has been recognized as the most effective therapy to date that may modify the underlying disease course and provide long-term benefits for individuals refractory to pharmacotherapy. However, over the past 25 years, there has been substantial growth in developing alternative therapies to traditional SCIT. Areas covered : This article will review the most current literature focusing on advancements of AR therapies. Novel AR therapies that are currently under investigation include: the addition of omalizumab, an anti-immunoglobulin E (IgE) monoclonal antibody (mAb), to SCIT; altering the method of delivery of allergen immunotherapy (AIT) including sublingual (SLIT), epicutaneous (EIT), intralymphatic (ILIT), intranasal (INIT) and oral mucosal immunotherapy (OMIT); use of capsaicin spray; novel H3 and H4 antihistamines; activation of the innate immune system through Toll-like receptor agonists; and the use of chemically altered allergens, allergoids, recombinant allergens and relevant T-cell epitope peptides to improve the efficacy and safety of AIT. Expert opinion : These promising novel therapies may offer more effective and/or safer treatment options for AR patients, and in some instances, induce immunologic tolerance.